2016
DOI: 10.5713/ajas.15.0836
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Single Nucleotide Polymorphisms Associated with Carcass Traits in a Commercial Hanwoo Population

Abstract: Four carcass traits, namely carcass weight (CW), eye muscle area (EMA), back fat thickness (BF), and marbling score (MS), are the main price decision parameters used for purchasing Hanwoo beef. The development of DNA markers for these carcass traits for use in a beef management system could result in substantial profit for beef producers in Korea. The objective of this study was to validate the association of highly significant single nucleotide polymorphisms (SNPs) identified in a previous genome-wide associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The fact that PDE4D was downregulated in HIF animals may increase the intracellular cAMP through the regulation of other genes and thus may contribute to an increase in IF content and maintain immune homeostasis of Nelore cattle. PDE4D was previously related with marbling score in a commercial Hanwoo cattle population from genome-wide association study (GWAS) [64].…”
Section: Resultsmentioning
confidence: 99%
“…The fact that PDE4D was downregulated in HIF animals may increase the intracellular cAMP through the regulation of other genes and thus may contribute to an increase in IF content and maintain immune homeostasis of Nelore cattle. PDE4D was previously related with marbling score in a commercial Hanwoo cattle population from genome-wide association study (GWAS) [64].…”
Section: Resultsmentioning
confidence: 99%
“…The PIK3R1 gene has been associated with an increased milk protein fraction at peak lactation [ 38 ]. The PDE4D gene has been reported to increase meat marbling in studies on Nellore and Hanwoo cattle [ 39 ]. Genes related to immunity and environmental resistance have been identified on BTA20; for example, the candidate gene CD180 is associated with the animal’s ability to deal with pathogens in Brahman and Angus cattle [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…To estimate the contribution of the genome-wide significant SNPs to the genetic variance based on the GRM calculated from all eligible SNPs, the percentage of genetic contribution ( ) accounted for by each SNP was calculated using the following formula ( Sudrajad et al, 2016 ; Bhuiyan et al, 2018 ): where p and q are the observed allele frequencies for the SNP in the current population, is the additive effect of the SNP, and is the additive genetic variance for a given trait estimated in the linear mixed model.…”
Section: Methodsmentioning
confidence: 99%